Suolo, sistemi locali di produzione ed agricoltura nello sviluppo rurale delle economie post-industriali - Alessandro Romagnoli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
– The post-industrial development of non-urban territory shows a decline in the agricultural use of the land and a rise of industrial and services activities localization on it. This imply a new methodology to study rural and agricultural development. The aim of the paper is to provide a general framework to deal with these problems. The starting point is the use of soil as an input of production and as a space of the localization strategies of the firm.
Keywords: 330